1965
DOI: 10.5006/0010-9312-21.9.277
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Polarization Behavior Of Nickel-Chromium Alloys In Sulfuric Acid Solutions

Abstract: A polarization behavior of chromium was investigated in H2SO4-Na2SO4 solution of pH 2.0 at 298 K by the potentiostatic oxidation and electrode impedance technique. From the coulometry and the chemical analysis of electrolyte the thickness of the passive films on chromium was estimated to be about 2.1 nm after 3.6 ks potentiostatic oxidation. The frequency response of the electrode impedance were simulated by the equivalent circuit of a cascade connection of two parallel RC in the prepassive (the potential regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 2 publications
3
11
0
Order By: Relevance
“…8a͒. Myers et al found that addition of 9 wt % Cr ͑about 10 atom % Cr͒ markedly reduced the critical current density for passivation and significantly reduced active current densities, 23 consistent with the XANES ͑described above͒ and the electrochemical behavior ͑Fig. 1͒ in this work.…”
Section: Discussionsupporting
confidence: 90%
“…8a͒. Myers et al found that addition of 9 wt % Cr ͑about 10 atom % Cr͒ markedly reduced the critical current density for passivation and significantly reduced active current densities, 23 consistent with the XANES ͑described above͒ and the electrochemical behavior ͑Fig. 1͒ in this work.…”
Section: Discussionsupporting
confidence: 90%
“…2,3 This enhanced passivity is generally attributed to a higher concentration of Cr(III) in the inner oxide layer than in the substrate alloy 4 due to the growth and defect annealing of a Cr(III) oxide barrier layer at the alloy/oxide interface. X-ray photoelectron spectroscopy (XPS) and scanning-tunneling microscopy (STM) have shown that the passive fi lm (on Cr, Fe-Cr, Fe-Cr-Ni, and Ni-Cr metals and alloys) consists primarily of an inner layer of Cr 2 O 3 and an outer layer of Cr(OH) 3 .…”
Section: Introductionmentioning
confidence: 98%
“…The impact of Ni concentration in the composition of the steel on the formation and dissolution of the passive layer is usually considered to be insignificant, Ni serving to stabilize the austenitic phase without affecting the corrosion resistance. 31 Based on these results, a structure for the oxide layer of the X1CrNiSi18-15-4 SS is proposed and characterized by its n Cr /n Si molar ratio.…”
mentioning
confidence: 99%